2023
DOI: 10.3390/s23073673
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Skin-Wearable Sensors for Non-Invasive Health Monitoring Applications

Abstract: The early detection of fatal diseases is crucial for medical diagnostics and treatment, both of which benefit the individual and society. Portable devices, such as thermometers and blood pressure monitors, and large instruments, such as computed tomography (CT) and X-ray scanners, have already been implemented to collect health-related information. However, collecting health information using conventional medical equipment at home or in a hospital can be inefficient and can potentially affect the timeliness of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 231 publications
0
11
0
Order By: Relevance
“…It was observed that pure liquid VOCs showed less permeability due to the dehydration of the stratum corneum. 104,105 Increased skin temperature enhances percutaneous absorption proportionally. In most studies, skin absorption measurements were conducted in temperature-controlled experiments.…”
Section: Skin-emitted Volatolomes and Their Association With Diseasesmentioning
confidence: 99%
“…It was observed that pure liquid VOCs showed less permeability due to the dehydration of the stratum corneum. 104,105 Increased skin temperature enhances percutaneous absorption proportionally. In most studies, skin absorption measurements were conducted in temperature-controlled experiments.…”
Section: Skin-emitted Volatolomes and Their Association With Diseasesmentioning
confidence: 99%
“…In recent years, novel OPAMP architectures have emerged [18][19][20][21] aiming to enhance their functionality for specific domains. One such critical domain is biomedical electronics, where OPAMPs play a crucial role [22] and serve as fundamental building blocks. In biomedical electronic circuits, OPAMPs need to address the unique features demanded by bio-potential signals (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, novel OPAMP architectures have emerged [19][20][21][22][23], aiming to enhance their functionality for specific domains. One such critical domain is biomedical electronics, where OPAMPs play a crucial role [24] and serve as fundamental building blocks. In biomedical electronic circuits, OPAMPs need to address the unique features demanded by bio-potential signals (i.e., ECG, EEG, EMG), which include high amplification (as these signals are inherently weak), low noise levels (to ensure accurate signal acquisition and subsequent processing), and low power consumption.…”
Section: Introductionmentioning
confidence: 99%